Waste Reduction in Bottled Water Production Process - Ponpakdee, Suwanna (Engineering and Technology Horizons, 2021)
The purpose of this research is to find and eliminate eight wastes of the Lean way by applying Value Stream Mapping (VSM) method to bottled water process. The key performance indicator for this research is the Lead Time (LT) for this industry, which has four main processes: water treatment, filling water to bottle, packaging to pallet and shipping to customer. The results of the current value stream mapping after analyzed the wastes found that two main wastes came from excessive processing and inventory. To reduce the effect of these wastes, the process improvement like a new design-scale for counting pallet sheets, the change of an accurate design-function for to filling in the MS-Excel file, was taken into account for eliminating the excessive process waste; moreover, and applied of Economic Production Quantity (EPQ) to eliminate the oversize of the inventory waste. The good results were found that the lead time of the bottled water industry will be decreased from 230,598 seconds to 228,588 seconds (reduced 33.5 minutes) or 0.88 percent